Grand challenge: social psychology without hubris - Jost, John T. (Frontiers in Social Psychology, 2024)
In this editorial, the Founding Field Chief Editor of Frontiers in Social Psychology expresses several ideas about the past, present, and possible future of social psychology, seeking to explain we need social psychology, why we need a new journal in social psychology, and what kind of journal in social psychology we need. The Editor argues for a rich, humanistic, interdisciplinary, philosophically informed social psychology devoted to addressing social problems in the illustrious traditions of John Dewey, Kurt Lewin, Gordon Allport, Muzafer Sherif, Solomon Asch, Morton Deutsch, and others. He suggests that disciplinary “crises” of practicality, historicity, and replicability may be more interconnected than is generally recognized. The Editor advocates a non-hubristic, theory-driven, multi-leveled analysis of human behavior that attends to both subjective and objective aspects of social, cultural, economic, and political contexts. Editorial priorities of the new journal include scientific rigor, social relevance, and intellectual humility.